Searching behaviour in Chilocorus nigritus (F.) (Coleoptera: Coccinellidae) - Boothe, R A; Ponsonby, D J (Communications in agricultural and applied biological sciences, 2006)
Chilocorus spp are generalist predators of armoured scale insects. C. nigritus is a common predator; however there are several gaps in the literature regarding aspects of its behaviour and general ecology. The study was conducted in order to examine the foraging behaviour of this coccidophagous species on the biparental strain of the diaspid, Aspidiotus nerii Bouché (Homoptera: Diaspididae), a widely distributed polyphagous pest. Unlike many other Coccoidea, diaspids do not produce honeydew and the main aim of the experiment was to establish whether C. nigritus use stimuli other than visual cues in prey location. Twenty to twenty eight day old female C. nigritus maintained on a culture of A nerii at 26 +/- 1 degrees C and R.H. of 45 +/- 10 % were offered five treatments with twenty minutes between treatments. The treatments offered were; host plant only, host plant with scale insect wash, overlapping generations of scales, host plant with scales removed, and plain filter paper. Beetle search behaviours were observed for ten minutes, videotaped and analysed using video analysis software. Searching behaviour in the absence of the scale or its food plant (plain filter paper) served as control. Tests of within-subject contrasts of the various parameters examined showed that turning rate was higher and beetles arrested more on host plant material when scales were present and on host plants from which scales had been removed than on all other treatments. Analyses of behaviours suggest that beetles use either olfactory or contact chemoreception cues when locating their prey at plant surface level.